"France deserves to be free": constituting Frenchness in Marine Le Pen's National Front/National Rally - Seitz, Lauren, author; Anderson, Karrin, advisor; Khrebtan-Hörhager, Julia, committee member; Daum, Courtenay, committee member (Colorado State University. Libraries, 2020)
This thesis employs constitutive rhetoric to analyze French far-right politician Marine Le Pen's discourse. Focusing on ten of Le Pen's speeches given between 2015 and 2019, I argue that Le Pen made use of Kenneth Burke's steps of scapegoating and purification as a way to rewrite French national identity and constitute herself as a revolutionary political leader. Le Pen first identified with the subjects and system that she scapegoats. Next, she cast out elites, globalists, and immigrants, identifying them as scapegoats of France's contemporary identity split. Finally, by disidentifying with the scapegoats, Le Pen constituted her followers as always already French patriots and herself as her leader. This allowed her to propose a new form of French national identity that was undergirded by far-right ideals and discourse of revolution. This thesis presents several implications for understanding contemporary French national identity, the far right, and women politicians. It also contributes to the project of internationalizing public address research in Communication Studies.
France deserves to be free: constituting Frenchness in Marine Le Pen's National Front/National Rally
Keywords: far right; Le Pen, Marine; reactionary nationalism; France; constitutive rhetoric; national identity